Socio-demographic determinants of treatment outcome in multidrug resistant tuberculosis cases registered under Programmatic management of drug resistant tuberculosis services in Amritsar, Punjab - Nagpal, Manisha; Chawla, Sarthak; Devgun, Priyanka; Chawla, Naresh (International Journal Of Community Medicine And Public Health, 2019)
Background: Multidrug resistant tuberculosis (MDR-TB) has become a major public health problem. It is associated with significant morbidity and mortality. The treatment success rate worldwide is around 50%. Methods: This cross-sectional study was conducted on all MDR-TB patients who were registered and being treated under PMDT services in Amritsar district from 1st April 2014 to 31st March 2015. The treatment outcome with their socio-demographic determinants was ascertained. Data management and analysis was done by using Microsoft excel and SPSS. Results: Out of 87 MDR-TB patients, 57 (65.5%) were males and 30 (34.4%) were females. The various treatment outcomes observed were- 30 (34.5%) cured, 19 (21.8%) treatment completed, 18 (20.7%) died, 13 (14.9%) defaulted, 4 (4.6%) shifted to XDR TB regime and 3 (3.4%) failure. Conclusions: On statistical analysis, it was observed that age (p=0.000), marital status (p=0.024), educational status (p=0.011) and occupation (p=0.002) were significantly associated with the treatment outcome. Other factors like sex, type of family and socio-economic status did not affect the treatment outcome.